If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -78 = 6U + 12 Reorder the terms: -78 = 12 + 6U Solving -78 = 12 + 6U Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Add '-6U' to each side of the equation. -78 + -6U = 12 + 6U + -6U Combine like terms: 6U + -6U = 0 -78 + -6U = 12 + 0 -78 + -6U = 12 Add '78' to each side of the equation. -78 + 78 + -6U = 12 + 78 Combine like terms: -78 + 78 = 0 0 + -6U = 12 + 78 -6U = 12 + 78 Combine like terms: 12 + 78 = 90 -6U = 90 Divide each side by '-6'. U = -15 Simplifying U = -15
| 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x | | -2(-4+y)-5y=15 | | -13+4b=-3b-7 | | 4x-3+2x+53=90 | | y=5x^2+2x-1 | | -3(g-9)+-9=-9 | | 4x-3+2x+53=180 | | 3x+x-2=-x+7 | | 2(p-4)-3=9 |